How do you use substitution to integrate #e^x * sin2xdx #?

Answer 1

# int \ e^(x)sin2x \ dx = 1/5e^x(sin2x - 2cos2x) + C #

We seek the integral:

# I =int \ e^(x)sin2x \ dx #

There is no suitable substitution, however, We can apply Integration By Parts:

Let # { (u,=sin2x, => (du)/dx,=2cos2x), ((dv)/dx,=e^x, => v,=e^x ) :}#

Then plugging into the IBP formula:

# int \ (u)((dv)/dx) \ dx = (u)(v) - int \ (v)((du)/dx) \ dx #

We have:

# int \ (sin2x)(e^x) \ dx = (sin 2x)(e^x) - int \ (e^x)(2cos 2x) \ dx #
# :. I = e^(2x)sin2x - 2 \ int \ e^xcos 2x \ dx #

Now consider the integral given by:

# I_2 = int \ e^xcos 2x \ dx #

We will now need to apply IBP again:

Let # { (u,=cos2x, => (du)/dx,=-2sin2x), ((dv)/dx,=e^x, => v,=e^x ) :}#

Then plugging into the IBP formula we have::

# int \ (cos2x)(e^x) \ dx = (cos2x)(e^x) - int \ (e^x)(-2sin2x) \ dt #
# I_2 = e^xcos2x + 2 \ int \ e^xsin2x \ dt # # \ \ \ = e^xcos2x + 2I #

And so combining the results we find that:

# I = e^xsin2x - 2{e^xcos2x + 2I} # # \ \ = e^xsin2x - 2e^xcos2x - 4I #
# :. 5I = e^x(sin2x - 2cos2x) #
# :. I = 1/5e^x(sin2x - 2cos2x) #

And not forgetting the constant of integration,

# I = 1/5e^x(sin2x - 2cos2x) + C #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To integrate e^x * sin(2x) dx using substitution, let u = sin(2x), then du = 2cos(2x) dx. Rearranging, dx = du / (2cos(2x)). Now, substitute u and dx in terms of u into the integral:

∫ e^x * sin(2x) dx = ∫ e^x * u * (1/2cos(2x)) du = (1/2) ∫ e^x * u / cos(2x) du = (1/2) ∫ e^x * u / (1 - 2sin^2(x)) du = (1/2) ∫ e^x * u / (1 - 2u^2) du

This integral can be further simplified using partial fractions or other methods, but the initial substitution is the key step in solving this integral.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7